2019
DOI: 10.1002/jcla.23004
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐derived exosomal miRNA‐320d as a biomarker for metastatic colorectal cancer

Abstract: Background To identify specific exosomal microRNAs (miRNAs) as serum biomarkers for prediction of metastasis in patients with colorectal cancer (CRC). Materials and Methods Serum exosomes were isolated from patients with metastatic CRC (n = 34) and non‐metastatic CRC (n = 108) by ultracentrifugation and characterized using transmission electron microscopy, qNano, and Western blot. Differential exosomal miRNAs were screened by sequencing and validated by qPCR in metastatic and non‐metastatic CRC patients. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 34 publications
2
60
0
Order By: Relevance
“…This was in agreement with the results of TEM, that isolated serum exosomes had a spherical morphology with a diameter of 50-150 nm as indicated in Figure 1B. In addition, western immunoblotting con rmed the two well-known protein markers, including CD63 and TSG101 [19,22], which were enriched in exosomes but absent in cell extracts ( Figure 1C). Besides, GM130 as a negative control was only detected in the cell extracts but not in exosomes [20].…”
Section: Identi Cation Of Isolated Serum Exosomessupporting
confidence: 90%
See 2 more Smart Citations
“…This was in agreement with the results of TEM, that isolated serum exosomes had a spherical morphology with a diameter of 50-150 nm as indicated in Figure 1B. In addition, western immunoblotting con rmed the two well-known protein markers, including CD63 and TSG101 [19,22], which were enriched in exosomes but absent in cell extracts ( Figure 1C). Besides, GM130 as a negative control was only detected in the cell extracts but not in exosomes [20].…”
Section: Identi Cation Of Isolated Serum Exosomessupporting
confidence: 90%
“…Serum biomarkers for diagnosis of NSCLC patients have been widely studied and applied in clinical, such as CEA, CA125, NSE, CYFRA21-1, and CA153 [19,20]. However, there is no any effective biomarker for diagnosis of early-stage NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, miR-320d was found to significantly distinguish patients with metastatic CRC from those who were non-metastatic with a sensitivity of 62% and a specificity of 64.7%. When it was combined with CEA, the sensitivity and specificity rose to 63.3% and 91.3%, respectively [92]. In summary, these miRs could be utilized as potential diagnostic markers of CRC, whereby some are diagnostic of early stages, while others of distant metastatic disease.…”
Section: Diagnostic Biomarkersmentioning
confidence: 94%
“…In CRC, miR-1246 was also found to be significantly increased in CRC tissues, and functioned as a tumor promoting factor through inducing cell proliferation, migration, invasion and chemoresistance 24,25 . Moreover, some specific exosomal microRNAs (miRNAs), including miR-1246, were identified as a biomarker for metastatic colorectal cancer [26][27][28] . In addition, Peng et al demonstrated that miR-1246/SPRED2/MAPK axis played an important role in the progression of CRC 29 .…”
Section: Dusp9 Expression Is Silenced Via Promoter Hypermethylation Inmentioning
confidence: 99%